Information systems essentials - Haag, Stephen (McGraw-Hill, 2006)
A concise, four-color IS concepts book with a lively, contemporary writing style at a student-friendly price. Information Systems Essentials Information Systems Essentials comes with more and better ancillaries than any other essentials text. An additional unique feature is the opening unit, explaining the benefit and impact of IS on each business career. This chapter addresses the frequently-cited problem of effectively showing students the relevance of this course. Information Systems Essentials includes the first nine chapters from Haag MIS 5e, representing what introductory MIS students should definitely know. An appendix includes the two XLMs from Haag MIS 5e: hardware/software and telecommunications.